Estudio de caso sobre el impacto de las herramientas digitales en una empresa chocolatera: - Vega Granda, Ricardo; Cabezas García, David; Rosales Pintado , Fabian; Granda Martínez, Jannette; Ortega Pindo, Azucena (EASI: Engineering and Applied Sciences in Industry, 2025)
This study analyzes the impact of digital tools on production processes in a chocolate industry company in Ecuador, within the broader context of Industry 4.0. Through a qualitative and descriptive approach, semi-structured interviews were conducted with ten employees working in production and administration. The objective was to explore the perceived benefits, challenges, and operational changes associated with the integration of digital technologies. The research followed a non-experimental, inductive design, and used Atlas.ti for thematic coding and qualitative analysis. The results reveal that digital tools have significantly transformed core areas such as production, distribution, and marketing. The most used technologies include management software, machinery sensors, CRM systems, and social media platforms. Participants highlighted improvements in efficiency, error reduction, and resource optimization, as well as challenges related to staff training and technological adaptation. This study contributes empirical evidence on how digitalization unfolds in small and medium-sized enterprises in emerging economies. It also offers insights into the design of inclusive innovation strategies and context-specific policies to support digital transformation, particularly in the food sector.
Keywords: Digital tools; digitalization; production; industry; digital transformation